THE INFLUENCE OF FINANCIAL LITERACY, PARENTS' SOCIO-ECONOMIC STATUS, AND LIFESTYLE ON CONSUMPTIVE BEHAVIOR OF ADOLESCENTS - Muh Fahrurrozi; Muhammad Rapii; Baiq Intan Fuji Lestari (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2022)
Consumptive behavior of adolescents causes them not to thought long in bought things that were not really needed. The purpose of this study was to find out (1) the consumptive behavior of junior high school students, and (2) the influence of financial literacy, socio-economics, and lifestyle on the consumptive behavior of junior high school adolescents. Where this research uses a quantitative approach with the ex post facto method with a total sample of 36 students. Collecting data using tests, questionnaires and documentation and questionnaires. Data analysis used multiple linear regression. The results of the descriptive analysis showed that the level of adolescent consumptive behavior was 64% having moderate consumptive behavior, 22% adolescents having consumptive behavior in the high category, and 14% in the low category. The results showed that there was a significant influence between financial literacy, socioeconomic and lifestyle on consumptive behaviorPerilaku konsumtif remaja mengakibatkan remaja tidak berpikir panjang dalam membeli barang yang sebenarnya tidak dibutuhkan. Tujuan penelitian ini adalah untuk mengetahui (1) perilaku konsumtif pada remaja siswa Sekolah Menengah Pertama (SMP) dan (2) pengaruh literasi keuangan, sosial ekonomi, dan gaya hidup terhadap perilaku konsumitf remaja Sekolah Menengah Pertama. Dimana penelitian ini dengan menggunakan pendekatan kuantitatif dengan metode ex post facto dengan jumlah sampel penlitian yaitu 36 siswa. Pengumpulan data menggunakan tes, kuesioner dan dokumentasi. Analisis data menggunakan regresi linear berganda. Hasil analisis deskriptif menunjukkan bahwa tingkat perilaku konsumtif remaja adalah 64% memiliki perilaku konsumtif sedang, 22% remaja memiliki perilaku konsumtif kategori tinggi, dan 14% kategori rendah. Hasil penelitian menunjukan bahwa terdapat pengaruh yang signifikan antara literasi keuangan, sosial ekonomi dan gaya hidup terhadap perilaku konsumtif.